Residual Renal Function in Children Treated with Chronic Peritoneal Dialysis - Maria Roszkowska-Blaim; Piotr Skrzypczyk (The Scientific World Journal)
Residual renal function (RRF) in patients with end-stage renal disease (ESRD) receiving renal replacement therapy is defined as the ability of native kidneys to eliminate water and uremic toxins. Preserved RRF improves survival and quality of life in adult ESRD patients treated with peritoneal dialysis. In children, RRF was shown not only to help preserve adequacy of renal replacement therapy but also to accelerate growth rate, improve nutrition and blood pressure control, reduce the risk of adverse myocardial changes, facilitate treatment of anemia and calcium-phosphorus balance abnormalities, and result in reduced serum and dialysate fluid levels of advanced glycation end-products. Factors contributing to RRF loss in children treated with peritoneal dialysis include the underlying renal disease such as hemolytic-uremic syndrome and hereditary nephropathy, small urine volume, severe proteinuria at the initiation of renal replacement therapy, and hypertension. Several approaches can be suggested to decrease the rate of RRF loss in pediatric patients treated with chronic peritoneal dialysis: potentially nephrotoxic drugs (e.g., aminoglycosides), episodes of hypotension, and uncontrolled hypertension should be avoided, urinary tract infections should be treated promptly, and loop diuretics may be used to increase salt and water excretion.